2013
DOI: 10.1177/1557988313508303
|View full text |Cite
|
Sign up to set email alerts
|

Differential Impact of Types of Social Support in the Mental Health of Formerly Incarcerated Latino Men

Abstract: The role of social support in the mental health of formerly incarcerated Latino men (FILM) is an issue overlooked in public health prevention efforts. The objectives of this analysis were to (a) describe the levels of social support perceived and received by FILM; (b) identify the associations, if any, between levels of social support and mental health indicators such as depression and anxiety; and (c) explore the impact of familism and hypermasculinity on the receptivity of social support and the potential ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 66 publications
3
47
0
1
Order By: Relevance
“…Social support is an important factor in mental health and emotional well-being. A number of studies have shown that social support correlates with health maintenance [23], well-being [24], life satisfaction [25] positive and negative mood [26], mental stability and clarity [27] and better mental health outcomes [28]. Many researchers suggest that social support creates a buffer against effects of stressful and traumatic events [29,30] and produces higher levels of self-control and environmental stability [31].…”
Section: Social Support As a Factor Of Psychological Well-being And Ementioning
confidence: 99%
“…Social support is an important factor in mental health and emotional well-being. A number of studies have shown that social support correlates with health maintenance [23], well-being [24], life satisfaction [25] positive and negative mood [26], mental stability and clarity [27] and better mental health outcomes [28]. Many researchers suggest that social support creates a buffer against effects of stressful and traumatic events [29,30] and produces higher levels of self-control and environmental stability [31].…”
Section: Social Support As a Factor Of Psychological Well-being And Ementioning
confidence: 99%
“…Social support is protective against mental disorders and HIV-related drug use and sex risk among those involved in the criminal justice system [19][20][21][22]. In one study, social support indicators, such as social consistency, integration, and extensiveness, were protective against hard drug use and sexual risk behavior among former male inmates during the 6 months after release [19].…”
Section: Introductionmentioning
confidence: 99%
“…Support from family members, including parents, aunts, and children, has also demonstrated importance [20,21,[30][31][32]. For example, Muñoz-Laboy et al highlighted the role of family in protecting against depression, a consistent HIV risk factor, among formerly incarcerated Latino men [14,21,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This argument is supported by studies that have found that perceived support mediates the effect of structural support on mental health problems or is a stronger predictor of mental health problems [16,17,21,[58][59][60][61] or of health care utilization [62,63] than structural support. However, concerns have arisen that perceived social support might be influenced by negative mood states [64]. Thus, structural social support may potentially constitute a more ''objective'' way to measure social support because it is less influenced by concurrent mood.…”
Section: Introductionmentioning
confidence: 99%